Impact of hydrolysable and condensed tannin sources and levels on in vitro equine cecal fermentation - Lauren R. Wottlin; Robin C. Anderson; Raghavendra Bhatta; Jessica Leatherwood; Elena G. Olson; Todd R. Callaway; Steven C. Ricke (Research in Veterinary Science, 2025)

Re-focusing sampling, design and experimental methods to assess rapid evolution by non-native plant species - M. S. Lucas; I. Hensen; C. D. Barratt; R. M. Callaway; W. Durka; Y. Lekberg; D. U. Nagy; R. E. Onstein; M. A. Shah; N. M. van Dam; A. E. Thoma; C. Rosche (Biological Invasions, 2024)
Evolution can occur over contemporary timescales, which may be crucial for the invasive success of non-native plant species. Many studies have shown rapid evolution by comparing native and non-native populations in common gardens. However, our understanding of the mechanisms underpinning rapid evolution is still incomplete. Here, we identify the progress, applications, and limitations of studies on rapid evolution of non-native plants with respect to sampling, experimental design and experimental methods. To encompass broad variation within and between the ranges, we recommend sampling across large-scale environmental gradients. We also suggest careful consideration of pitfalls related to the choice of seed families and of the biotic interaction under focus. The latter should be chosen with a view on both the experimental treatment and the corresponding field data to estimate population history. Furthermore, we suggest exploiting multiple omics approaches to address the complexity of biotic interactions, and to account for non-adaptive evolution with molecular data on demographic history of populations. We also reviewed papers that studied rapid evolution in non-native plants and quantified how many of these met our criteria. We anticipate that disentangling adaptive and non-adaptive drivers of among-population variation can increase the accuracy of research on rapid evolution, and that integrating phenotypic, metabolomic and population genomic data can bring opportunities for studying complex biotic interactions. We also illustrate the importance of large collaborative networks and present our scientific network iCONNECT (integrative CONyza NEtwork for Contemporary Trait evolution), with the goal of motivating similar studies on the mechanistic understanding of rapid evolution.

Northward range expansions are not the full story: A case study of Sabellaria alveolata in Great Britain - Camille Domy; Rebecca Stone; Ruth Callaway; James C. Bull (Estuarine, Coastal and Shelf Science, 2023)

Comorbidity and Worse Outcome in Mildly Ill COVID-19 Outpatients - R. Pobee; T. Cable; D. Chan; J. Herrick; F. Korley; C. Callaway; M. Del-Rios (Journal of the Academy of Nutrition and Dietetics, 2023)

The EICA is dead? Long live the EICA ! - Ragan M. Callaway; Jacob E. Lucero; José L. Hierro; C. J. Lortie (Ecology Letters, 2022)
An important hypothesis for how plants respond to introduction to new ranges is the evolution of increased competitive ability (EICA). EICA predicts that biogeographical release from natural enemies initiates a trade‐off in which exotic species in non‐native ranges become larger and more competitive, but invest less in consumer defences, relative to populations in native ranges. This trade‐off is exceptionally complex because detecting concomitant biogeographical shifts in competitive ability and consumer defence depends upon which traits are targeted, how competition is measured, the defence chemicals quantified, whether defence chemicals do more than defend, whether ‘herbivory’ is artificial or natural, and where consumers fall on the generalist‐specialist spectrum. Previous meta‐analyses have successfully identified patterns but have yet to fully disentangle this complexity. We used meta‐analysis to reevaluate traditional metrics used to test EICA theory and then expanded on these metrics by partitioning competitive effect and competitive tolerance measures and testing Leaf‐Specific Mass in detail as a response trait. Unlike previous syntheses, our meta‐analyses detected evidence consistent with the classic trade‐off inherent to EICA. Plants from non‐native ranges imposed greater competitive effects than plants from native ranges and were less quantitatively defended than plants from native ranges. Our results for defence were not based on complex leaf chemistry, but instead were estimated from tannins, toughness traits and primarily Leaf‐Specific Mass. Species specificity occurred but did not influence the general patterns. As for all evidence for EICA‐like trade‐offs, we do not know if the biogeographical differences we found were caused by trade‐offs per se, but they are consistent with predictions derived from the overarching hypothesis. Underestimating physical leaf structure may have contributed to two decades of tepid perspectives on the trade‐offs fundamental to EICA.

Evidence for evolution of increased competitive ability for invasive Centaurea solstitialis, but not for naturalized C. calcitrapa - Daniel Montesinos; Ryan C. Graebner; Ragan M. Callaway (Biological Invasions, 2019)

Humic products in agriculture: potential benefits and research challenges—a review - Daniel C. Olk; Dana L. Dinnes; J. Rene Scoresby; Chad R. Callaway; Jerald W. Darlington (Journal of Soils and Sediments, 2018)

Solidago gigantea plants from nonnative ranges compensate more in response to damage than plants from the native range - Huixuan Liao; Priscila C. S. Gurgel; Robert W. Pal; David Hooper; Ragan M. Callaway (Ecology, 2016)
Resistance and tolerance are two ways that plants cope with herbivory. Tolerance, the ability of a plant to regrow or reproduce after being consumed, has been studied less than resistance, but this trait varies widely among species and has considerable potential to affect the ecology of plant species. One particular aspect of tolerance, compensatory responses, can evolve rapidly in plant species; providing insight into interactions between consumers and plants. However, compensation by invasive species has rarely been explored. We compared compensatory responses to the effects of simulated herbivory expressed by plants from seven Solidago gigantea populations from the native North American range to that expressed by plants from nine populations from the nonnative European range. Populations were also collected along elevational gradients to compare ecotypic variation within and between ranges. Solidago plants from the nonnative range of Europe were more tolerant to herbivory than plants from the native range of North America. Furthermore, plants from European populations increased in total biomass and growth rate with elevation, but decreased in compensatory response. There were no relationships between elevation and growth or compensation for North American populations. Our results suggest that Solidago gigantea may have evolved to better compensate for herbivory damage in Europe, perhaps in response to a shift to greater proportion of attack from generalists. Our results also suggest a possible trade‐off between rapid growth and compensation to damage in European populations but not in North American populations.

Survey of Clostridium difficile in retail seafood in College Station, Texas - Keri N. Norman; Roger B. Harvey; Kathleen Andrews; Michael E. Hume; Todd R. Callaway; Robin C. Anderson; David J. Nisbet (Food Additives & Contaminants: Part A, 2014)

Wetland Accretion Rate Model of Ecosystem Resilience (WARMER) and Its Application to Habitat Sustainability for Endangered Species in the San Francisco Estuary - Kathleen M. Swanson; Judith Z. Drexler; David H. Schoellhamer; Karen M. Thorne; Mike L. Casazza; Cory T. Overton; John C. Callaway; John Y. Takekawa (Estuaries and Coasts, 2014)

Alpine cushion plants inhibit the loss of phylogenetic diversity in severe environments - B. J. Butterfield; L. A. Cavieres; R. M. Callaway; B. J. Cook; Z. Kikvidze; C. J. Lortie; R. Michalet; F. I. Pugnaire; C. Schöb; S. Xiao; B. Zaitchek; F. Anthelme; et al. (Ecology Letters, 2013)
Biotic interactions can shape phylogenetic community structure (PCS). However, we do not know how the asymmetric effects of foundation species on communities extend to effects on PCS. We assessed PCS of alpine plant communities around the world, both within cushion plant foundation species and adjacent open ground, and compared the effects of foundation species and climate on alpha (within‐microsite), beta (between open and cushion) and gamma (open and cushion combined) PCS. In the open, alpha PCS shifted from highly related to distantly related with increasing potential productivity. However, we found no relationship between gamma PCS and climate, due to divergence in phylogenetic composition between cushion and open sub‐communities in severe environments, as demonstrated by increasing phylo‐beta diversity. Thus, foundation species functioned as micro‐refugia by facilitating less stress‐tolerant lineages in severe environments, erasing a global productivity – phylogenetic diversity relationship that would go undetected without accounting for this important biotic interaction.

Marsh Restoration: A Synthesis of Science and Management - John C. Callaway (Wetlands, 2013)

Evaluation of the Potential Antimicrobial Resistance Transfer from a Multi-Drug Resistant Escherichia coli to Salmonella in Dairy Calves - T. S. Edrington; R. L. Farrow; M. E. Hume; P. N. Anderson; G. R. Hagevoort; D. J. Caldwell; T. R. Callaway; R. C. Anderson; D. J. Nisbet (Current Microbiology, 2013)

Carbon Sequestration and Sediment Accretion in San Francisco Bay Tidal Wetlands - John C. Callaway; Evyan L. Borgnis; R. Eugene Turner; Charles S. Milan (Estuaries and Coasts, 2012)

Impact of Acroptilon repens on co-occurring native plants is greater in the invader’s non-native range - Ragan M. Callaway; Urs Schaffner; Giles C. Thelen; Aloviddin Khamraev; Tangirbergen Juginisov; John L. Maron (Biological Invasions, 2012)

Invasive species grows faster, competes better, and shows greater evolution toward increased seed size and growth than exotic non-invasive congeners - Ryan C. Graebner; Ragan M. Callaway; Daniel Montesinos (Plant Ecology, 2012)

Salinity and Inundation Influence Productivity of the Halophytic Plant Sarcocornia pacifica - Lisa M. Schile; John C. Callaway; V. Thomas Parker; Michael C. Vasey (Wetlands, 2011)

Patterns in Estuarine Vegetation Communities in Two Regions of California: Insights from a Probabilistic Survey - A. Elizabeth Fetscher; Martha A. Sutula; John C. Callaway; V. Thomas Parker; Michael C. Vasey; Joshua N. Collins; Walter G. Nelson (Wetlands, 2010)

Is there a risk to living large? Large size correlates with reduced growth when stressed for knapweed populations - Wei-Ming He; Giles C. Thelen; Wendy M. Ridenour; Ragan M. Callaway (Biological Invasions, 2010)

Decreased competiveness of the foodborne pathogen Campylobacter jejuni during Co-culture with the hyper-ammonia producing anaerobe Clostridium aminophilum - R. C. Anderson; M. D. Flythe; N. A. Krueger; T. R. Callaway; T. S. Edrington; R. B. Harvey; D. J. Nisbet (Folia Microbiologica, 2010)

Cell yields and fermentation responses of a Salmonella Typhimurium poultry isolate at different dilution rates in an anaerobic steady state continuous culture - Kingsley D. Dunkley; Todd R. Callaway; Corliss O’Bryan; Megan M. Kundinger; Claudia S. Dunkley; Robin C. Anderson; David J. Nisbet; P. G. Crandall; Steven C. Ricke (Antonie van Leeuwenhoek, 2009)

Effects of the Dicarboxylic Acids Malate and Fumarate on E. coli O157:H7 and Salmonella enterica Typhimurium Populations in Pure Culture and in Mixed Ruminal Microorganism Fermentations - David J. Nisbet; Todd R. Callaway; T. S. Edrington; Robin C. Anderson; N. Krueger (Current Microbiology, 2009)

Novel weapons and invasion: biogeographic differences in the competitive effects of Centaurea maculosa and its root exudate (±)-catechin - Wei-Ming He; Yulong Feng; Wendy M. Ridenour; Giles C. Thelen; Jarrod L. Pollock; Alecu Diaconu; Ragan M. Callaway (Oecologia, 2009)

Acyl-Homoserine-Lactone Autoinducer in the Gastrointesinal Tract of Feedlot Cattle and Correlation to Season, E. Coli O157:H7 Prevalence, and Diet - T. S. Edrington; R. L. Farrow; V. Sperandio; D. T. Hughes; T. E. Lawrence; T. R. Callaway; R. C. Anderson; D. J. Nisbet (Current Microbiology, 2009)

Concentrations of the Allelochemical (±)-Catechin IN Centaurea maculosa Soils - Laura G. Perry; Giles C. Thelen; Wendy M. Ridenour; Ragan M. Callaway; Mark W. Paschke; Jorge M. Vivanco (Journal of Chemical Ecology, 2007)

Reply to comment on our paper “evolution of tidal creek networks in a high sedimentation environment: A 5-year experiment at Tijuana Estuary, California” - John C. Callaway; Katy J. Wallace; Joy B. Zedler (Estuaries and Coasts, 2006)

Effect of Ractopamine HCl Supplementation on Fecal Shedding of Escherichia coli O157:H7 and Salmonella in Feedlot Cattle - T. S. Edrington; T. R. Callaway; S. E. Ives; M. J. Engler; T. H. Welsh; D. M. Hallford; K. J. Genovese; R. C. Anderson; D. J. Nisbet (Current Microbiology, 2006)

Effects of Ractopamine HCl on Escherichia coli O157:H7 and Salmonella In Vitro and on Intestinal Populations and Fecal Shedding in Experimentally Infected Sheep and Pigs - Thomas S. Edrington; Todd R. Callaway; David J. Smith; Ken J. Genovese; Robin C. Anderson; David J. Nisbet (Current Microbiology, 2006)

Oxalate contributes to the resistance of Gaillardia grandiflora and Lupinus sericeus to a phytotoxin produced by Centaurea maculosa - Tiffany L. Weir; Harsh Pal Bais; Valerie J. Stull; Ragan M. Callaway; Giles C. Thelen; Wendy M. Ridenour; Suresh Bhamidi; Frank R. Stermitz; Jorge M. Vivanco (Planta, 2006)

Insect herbivory stimulates allelopathic exudation by an invasive plant and the suppression of natives - Giles C. Thelen; Jorge M. Vivanco; Beth Newingham; William Good; Harsh P. Bais; Peter Landres; Anthony Caesar; Ragan M. Callaway (Ecology Letters, 2005)
Exotic invasive plants are often subjected to attack from imported insects as a method of biological control. A fundamental, but rarely explicitly tested, assumption of biological control is that damaged plants are less fit and compete poorly. In contrast, we find that one of the most destructive invasive plants in North America, Centaurea maculosa , exudes far higher amounts of (±)‐catechin, an allelopathic chemical known to have deleterious effects on native plants, when attacked by larvae of two different root boring biocontrol insects and a parasitic fungus. We also demonstrate that C. maculosa plants experimentally attacked by one of these biocontrols exhibit more intense negative effects on natives.

Resource degradation: a subtle effect of bottom fishing - M. J. Kaiser; H. Hinz; R. M. Callaway; A. Nall; C. L. Biles (Marine Biology, 2005)

Restoration of urban salt marshes: Lessons from southern California - John C. Callaway; Joy B. Zedler (Urban Ecosystems, 2004)

Biogeographical variation in community response to root allelochemistry: novel weapons and exotic invasion - Jorge M. Vivanco; Harsh P. Bais; Frank R. Stermitz; Giles C. Thelen; Ragan M. Callaway (Ecology Letters, 2004)
Centaurea diffusa is one of the most destructive invasive weeds in the western USA and allelopathy appears to contribute to its invasiveness ( Callaway & Aschehoug 2000 ). Here we identify a chemical from the root exudates of C. diffusa , 8‐hydroxyquinoline, not previously reported as a natural product, and find that it varies biogeographically in its natural concentration and its effect as an allelochemical. 8‐Hydroxyquinoline is at least three times more concentrated in C. diffusa ‐invaded North American soils than in this weed's native Eurasian soils and has stronger phytotoxic effects on grass species from North America than on grass species from Eurasia. Furthermore, experimental communities built from North American plant species are far more susceptible to invasion by C. diffusa than communities built from Eurasian species, regardless of the biogeographical origin of the soil biota. Sterilization of North American soils suppressed C. diffusa more than sterilization of Eurasian soils, indicating that North American soil biota may also promote invasion by C. diffusa . Eurasian plants and soil microbes may have evolved natural resistance to 8‐hydroxyquinoline while North American plants have not, suggesting a remarkable potential for evolutionary compatibility and homeostasis among plants within natural communities and a mechanism by which exotic weeds destroy these communities.

Hempseed as a nutritional resource: An overview - J. C. Callaway (Euphytica, 2004)

High-throughput transgene copy number estimation by competitive PCR - Anton S. Callaway; Rita Abranches; Jeffery Scroggs; George C. Allen; William F. Thompson (Plant Molecular Biology Reporter, 2002)

Removal of GABAergic inhibition alters subthreshold input in neurons in forepaw barrel subfield (FBS) in rat first somatosensory cortex (SI) after digit stimulation - Cheng X. Li; Joseph C. Callaway; Robert S. Waters (Experimental Brain Research, 2002)

Epiphyte host preferences and host traits: mechanisms for species-specific interactions - Ragan M. Callaway; Kurt O. Reinhart; Georgianne W. Moore; Darrin J. Moore; Steven C. Pennings (Oecologia, 2002)

Parasitic plants: parallels and contrasts with herbivores - Steven C. Pennings; Ragan M. Callaway (Oecologia, 2002)

Subjective effects and tolerability of the South American psychoactive beverage Ayahuasca in healthy volunteers - Jordi Riba; Antoni Rodríguez-Fornells; Gloria Urbano; Adelaida Morte; Rosa Antonijoan; Maria Montero; James C. Callaway; Manel J. Barbanoj (Psychopharmacology, 2001)

Californian Salt-Marsh Vegetation: An Improved Model of Spatial Pattern - Joy B. Zedler; John C. Callaway; Julie S. Desmond; Gabrielle Vivian-Smith; Gregory D. Williams; Gary Sullivan; Alice E. Brewster; Brian K. Bradshaw (Ecosystems, 1999)

Impact of a parasitic plant on the zonation of two salt marsh perennials - Ragan M. Callaway; Steven C. Pennings (Oecologia, 1998)